Sinergitas Wisata Gronjong Wariti dan Industri Kreatif Emping Melinjo dalam Meningkatkan Perekonomian Masyarakat - Risma Eka Nandika; Rinawati Zailani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2026)
Local economic development in the village is a major factor in sustainable development. This study aims to understand how tourism villages and creative industries can work together to improve the local community's economy. The method used is a qualitative research method with a descriptive approach. With in-depth techniques, data collection includes observation, interviews, and documentation studies. The results of this study indicate that the synergy between Gronjong Wariti tourism and the Emping Melinjo creative industry has great potential to improve the economy of the Mejono Village community in order to increase income, open job opportunities, and improve people's lives. However, there are several obstacles faced, including a lack of attention and support from the local government, minimal supporting facilities, low quality of human resources (HR), the use of simple production technology, and suboptimal promotion. The Emping Melinjo creative industry faces several serious challenges, such as limited quality raw materials, dependence on middlemen, and low public awareness of the village's potential. Relatively high product prices also reduce purchasing power. To address this, we need to strengthen marketing networks and seek more stable alternative sources of raw materials. Furthermore, business management is suboptimal. Therefore, strategies are needed to optimize this synergy, such as improving human resource quality, product quality, and promotion, enhancing management capabilities, developing supporting infrastructure, fostering product innovation, and developing a monitoring and evaluation system.